2018
DOI: 10.1055/s-0038-1677371
|View full text |Cite
|
Sign up to set email alerts
|

„I feel lonely“

Abstract: ZusammenfassungSelbstverletzendes Verhalten spielt eine wesentliche Rolle innerhalb der Borderline-Persönlichkeitsstörung (BPS). Während bereits Einiges zur Funktion von selbstverletzendem Verhalten bekannt ist, gibt es wenig Studien über die damit assoziierten Gefühle oder mentalen Bilder. In der hier vorgestellten Studie wurden Patientinnen mit BPS hinsichtlich ihrer Gefühle bei der Ausführung selbstschädigender Verhaltensweisen befragt. Die Patientinnen berichteten überwiegend negative Gefühle, auf welche d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Although auto-aggression directly relates to the EDB construct, which was targeted by our intervention, loneliness could reflect a more indirect proxy of EDB. Loneliness is reported to precede self-harming behaviors (21,56), which in turn are carried out for the sake of emotion regulation. Although our results do not allow for similar causal inference, we still cannot rule out that successful application of IR may not only improve functional emotion regulation strategies (making EDB less frequent) but also enhance positive affect (leading to aversive feeling reduction, such as loneliness).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although auto-aggression directly relates to the EDB construct, which was targeted by our intervention, loneliness could reflect a more indirect proxy of EDB. Loneliness is reported to precede self-harming behaviors (21,56), which in turn are carried out for the sake of emotion regulation. Although our results do not allow for similar causal inference, we still cannot rule out that successful application of IR may not only improve functional emotion regulation strategies (making EDB less frequent) but also enhance positive affect (leading to aversive feeling reduction, such as loneliness).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of 10 self-injuring adults indicated that their first mental image about self-harm amplified the urge to self-injure and occurred directly after the first self-harm attempt (19). Increased levels of mental imagery are associated with suicidal ideation (20) and self-harming behavior (21). In a sample of inpatients and outpatients suffering from BPD, almost 68% reported intrusive mental imagery about EDB (21), and about 91% of the mental images were prospective in nature, regarding future episodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to consider that the presented cutoff values are limited to a German population of people suffering from mood and anxiety disorders. Knowing that intrusive imagery also plays a crucial role within social phobia (6), or BPD (38), future studies could hence focus on adapting the IFES to the aforementioned psychiatric disorders. The here presented study further abstained from conducting a factorial analysis testing for the three-factorial structure as presented within the IES (40, 41), on which the original IFES (11) is based, due to the fact that the authors of the original IFES did not confirm this three-factorial structure.…”
Section: Discussionmentioning
confidence: 99%
“…Adding more scientific findings about prospective intrusive imagery within personality disorders, specifically within BPD, a recent study showed that 67% of all investigated BPD patients reported the presence of mental images of self-harm, however, only 9% of these images were retrospective, but 42% were prospective images of self-harm (38). Moreover, the same study revealed that these vivid imageries about self-harm were serving as precursors of the actual execution of self-harming behavior, suggesting that the assessment of intrusive prospective imagery could be an essential tool in the treatment of nonsuicidal self-harming behavior.…”
Section: Introductionmentioning
confidence: 99%